Concise Review: Stem Cell Trials Using Companion Animal Disease Models. (3rd May 2016) - Hoffman, Andrew M.; Dow, Steven W.
Abstract: Studies to evaluate the therapeutic potential of stem cells in humans would benefit from more realistic animal models. In veterinary medicine, companion animals naturally develop many diseases that resemble human conditions, therefore, representing a novel source of preclinical models. To understand how companion animal disease models are being studied for this purpose, we reviewed the literature between 2008 and 2015 for reports on stem cell therapies in dogs and cats, excluding laboratory animals, induced disease models, cancer, and case reports. Disease models included osteoarthritis, intervertebral disc degeneration, dilated cardiomyopathy, inflammatory bowel diseases, Crohn's fistulas, meningoencephalomyelitis (multiple sclerosis-like), keratoconjunctivitis sicca (Sjogren's syndrome-like), atopic dermatitis, and chronic (end-stage) kidney disease. Stem cells evaluated in these studies included mesenchymal stem-stromal cells (MSC, 17/19 trials), olfactory ensheathing cells (OEC, 1 trial), or neural lineage cells derived from bone marrow MSC (1 trial), and 16/19 studies were performed in dogs. The MSC studies (13/17) used adipose tissue-derived MSC from either allogeneic (8/13) or autologous (5/13) sources. The majority of studies were open label, uncontrolled studies. Endpoints and protocols were feasible, and the stem cell therapies were reportedly safe and elicited beneficial patient responses in all but two of the trials. In conclusion, companion animals with naturally occurring diseases analogous to human conditions can be recruited into clinical trials and provide realistic insight into feasibility, safety, and biologic activity of novel stem cell therapies. However, improvements in the rigor of manufacturing, study design, and regulatory compliance will be needed to better utilize these models. Abstract : Companion animal diseases (reviewed in Table 1 ) have the potential to serve as realistic models of human disease, as they more closely approximate the natural history, symptoms, pathology, biomarkers, therapeutic responses, tolerance to therapies, and survival characteristics of analogous human conditions. Stem cell trials in companion animal disease models are, therefore, of interest as translational systems in regenerative medicine. We reviewed the study design, manufacturing, endpoints, safety, and efficacy data from stem cell trials in dogs and cats between the years of 2008-2015 ( n = 19) (Table 2 ). Most clinical trials were open label design involving MSC (see Cells Evaluated ), informing safety, route of administration, feasibility of protocols with modest power to evaluate efficacy. Overall safety was excellent, and patients showed responses that exceeded expectations based on baseline, historical, or interventional (placebo) controls. Companion animal disease models have potential to inform hypotheses concerning stem cell trials in humans. Improved rigor in study design and manufacturing will unmask the full potential of this approach to benefit humans and animals.